61.4k views
3 votes
Ap calculus ab. I'm completely lost

Ap calculus ab. I'm completely lost-example-1
User Shanton
by
6.3k points

1 Answer

0 votes

Answer:


\displaystyle f'(0) = (4)/(3)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Terms/Coefficients
  • Factoring
  • Functions
  • Function Notation
  • Exponential Rule [Rewrite]:
    \displaystyle b^(-m) = (1)/(b^m)

Calculus

Derivatives

Derivative Notation

Derivative Property [Multiplied Constant]:
\displaystyle (d)/(dx) [cf(x)] = c \cdot f'(x)

Derivative Property [Addition/Subtraction]:
\displaystyle (d)/(dx)[f(x) + g(x)] = (d)/(dx)[f(x)] + (d)/(dx)[g(x)]

Basic Power Rule:

  • f(x) = cxⁿ
  • f’(x) = c·nxⁿ⁻¹

Derivative Rule [Chain Rule]:
\displaystyle (d)/(dx)[f(g(x))] =f'(g(x)) \cdot g'(x)

Step-by-step explanation:

Step 1: Define

Identify


\displaystyle f(x) = (x^2 - 2x - 1)^\bigg{(2)/(3)}

Step 2: Differentiate

  1. Chain Rule:
    \displaystyle f'(x) = (d)/(dx)[(x^2 - 2x - 1)^\bigg{(2)/(3)}] \cdot (d)/(dx)[(x^2 - 2x - 1)]
  2. Basic Power Rule {Derivative Property - Subtraction]:
    \displaystyle f'(x) = (2)/(3)(x^2 - 2x - 1)^\bigg{(2)/(3) - 1} \cdot (2x^(2 - 1) - 2x^(1 - 1) - 0)
  3. Simplify:
    \displaystyle f'(x) = (2)/(3)(x^2 - 2x - 1)^\bigg{(-1)/(3)} \cdot (2x - 2)
  4. Rewrite [Exponential Rule - Rewrite]:
    \displaystyle f'(x) = \frac{2(2x - 2)}{3(x^2 - 2x - 1)^\bigg{(1)/(3)}}
  5. Factor:
    \displaystyle f'(x) = \frac{4(x - 1)}{3(x^2 - 2x - 1)^\bigg{(1)/(3)}}

Step 3: Evaluate

  1. Substitute in x [Derivative]:
    \displaystyle f'(0) = \frac{4(0 - 1)}{3[0^2 - 2(0) - 1]^\bigg{(1)/(3)}}
  2. [Order of Operations] Simplify:
    \displaystyle f'(0) = (4)/(3)

Topic: AP Calculus AB/BC (Calculus I/I + II)

Unit: Derivatives

Book: College Calculus 10e

User Noqrax
by
7.4k points